1998
DOI: 10.1089/neu.1998.15.473
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal Injection of Adenosine Agonists Protect Againstl-NAME Induced Neuronal Loss in the Rat

Abstract: Intraspinal injection of the nonspecific inhibitor of nitric oxide synthase N-nitro-L-arginine methyl ester (L-NAME) results in a dose-dependent loss of neurons in the rat spinal cord. This effect is thought to result from a reduction in basal levels of nitric oxide (NO), thereby producing an ischemic reaction secondary to vasoconstriction and reduced spinal cord blood flow (SCBF). An important component of this ischemic reaction is the release of excitatory amino acids and the initiation of an excitotoxic cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…We also showed that the thermal pain threshold in the lower extremities was significantly decreased in the SCI/CP groups, thus triggering hyperalgesia. These results indicated that both spontaneous and induced pain were induced in this rat model, in line with previous studies [ 30 32 ]. Treatment with DFO or arginine significantly increased the thermal pain threshold and reduced excessive grooming behavior, suggesting that these drugs relieved the induced and spontaneous SCI-associated CP.…”
Section: Discussionsupporting
confidence: 93%
“…We also showed that the thermal pain threshold in the lower extremities was significantly decreased in the SCI/CP groups, thus triggering hyperalgesia. These results indicated that both spontaneous and induced pain were induced in this rat model, in line with previous studies [ 30 32 ]. Treatment with DFO or arginine significantly increased the thermal pain threshold and reduced excessive grooming behavior, suggesting that these drugs relieved the induced and spontaneous SCI-associated CP.…”
Section: Discussionsupporting
confidence: 93%
“…Pretreatment with L‐NAME causes deterioration of hind‐limb motor dysfunction, whereas posttreatment with it reduces motor disturbance, suggesting that • NO formation by constitutive NOS protects against ischemia/reperfusion damage and that • NO produced by inducible NOS may be toxic. Intraspinal injection of L‐NAME induced a dose‐dependent loss of neurons in the rat spinal cord, further supporting the protective effect of constitutive • NO (Dora et al, 1998).…”
mentioning
confidence: 57%
“…2005) and in other pathological conditions (Sharma et al . 2005) have been already described in animal studies, although acute and chronic neurotoxic effects of this nitric oxide synthase inhibitor have also been reported (Dora et al . 1998; Ciani et al .…”
Section: Discussionmentioning
confidence: 91%
“…Pyruvate treatment decreased iNOS expression in astrocytes by about 50% (Ryu et al 2004), which may explain the partial prevention of creatine kinase activity inhibition and reinforces our present data indicating that this inhibition is at least in part mediated by formation of nitric oxide or its derivative peroxynitrite. In this regard, other neuroprotective actions of L-NAME in situations with energy deprivation, such as in cerebral ischemia (Margaill et al 1997) and hyperargininemia (Delwing et al 2003), as well as in a model of Parkinson's disease (Barthwal et al 2001;Kurosaki et al 2002;Singh et al 2005) and in other pathological conditions (Sharma et al 2005) have been already described in animal studies, although acute and chronic neurotoxic effects of this nitric oxide synthase inhibitor have also been reported (Dora et al 1998;Ciani et al 2001).…”
Section: Discussionmentioning
confidence: 99%